What Explains the Cost of Remittances ? An Examination Across 119 Country Corridors - Beck, Thorsten 1967- (The World Bank, 2009)
Remittances are a sizeable source of external financing for developing countries. In the L'Aquila 2009 G8 Summit, leaders pledged to reduce the cost of remittances by half in 5 years (from 10 to 5 percent). Yet, empirically, little is known about what drives the cost of remittances. Using newly gathered data across 119 country corridors, this paper explores the factors that determine the cost of remittances. Considering average costs across all types of institutions, the authors find that corridors with larger numbers of migrants and more competition among remittances service providers exhibit lower costs. By contrast, remittance costs are higher in richer corridors and in corridors with greater bank participation in the remittances market. Comparing results across all banks and all money transfer operators separately, the analysis finds few significant differences. However, estimations for Western Union, a leading player in the remittances business, suggest that this firm's prices are insensitive to competition